Bakti Sosial Penyerahan Sembako Bagi Masyarakat Terdampak Covid 19 Di Kelurahan Betungan Kota Bengkulu - Rachayu, Imma; Maryani , Desi; Lorita , Evi; Elfianty , Lena; Selviani , Diah; Luthfia , Izza (Jurnal Kewirausahaan dan Bisnis, 2021)
Based on the results of the activities and evaluation analysis, it can be concluded as follows The service participants were very enthusiastic about participating in the activities, which could increase the knowledge that was very useful for the people affected by covid-19 Bengkulu City and went home also getting the basic necessities they really needed. It is necessary to hold further community service with different materials so that they are more motivated in facing the covid - 19 pandemic era.